The Number of Years in Displacement and Gender as Mediating Factors of the Relation Between Ways of Confronting Psychological Stresses and Psychological Hardiness - Ola Darab Nasser (European Scientific Journal, ESJ, 2019)
This study employs the descriptive approach to identify the relationship between the ways of confronting stress and the psychological hardiness in displaced adolescents according to various variables. The main sample was selected randomly from the original study population. The sample consisted of (200) displaced adolescents (99 males and 101 females) from Sweida secondary schools. Two types of test instruments were used: The Psychological Hardiness Scale by (Nasser, 2012) and the Ways of Confronting Stresses Scale by (Al Abdallah, 2014). The psychometric properties of both scales were tested. To answer the study questions, the following statistics were used: Pearson correlation coefficient, t-test, one-way ANOVA Test, LSD test. The results indicate a positive correlation between the ways of confronting stresses and psychological hardiness. There was no significant difference between female and male students in terms of psychological hardiness, and neither was there any significant difference in Psychological hardiness according to age. The study also indicates differences between males and females in terms of denial. It seems that females are more denial than males and there are differences in the style of planning to solve problems according to age differences. The category (5 years and above) a higher degree of the planning to solve problems. The results of this research is likely to be a starting point for designing of the activities and training courses. Researchers should focus on the importance of psychological hardiness development programs as well as mental health practitioners should focus on the planning of integrated rehabilitation programs, furthermore they should pay more attention to social support, family unity, workshops and training courses for displaced adolescents.